Hubungan Jarak Rumah ke Fasilitas Kesehatan dan Dukungan Keluarga dengan Kontak Ibu Nifas Tahun 2019 - Norainah, Norainah; Isnaniah, Isnaniah; Barkinah, Tut (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2022)
Postpartum visits are an attempt to assess maternal and newborn health as well as to prevent, detect, and deal with problems that occur. Based on data from the Banjar District Health Office coverage of postpartum health services at Tatah Makmur Health Center in 2017 was 72.2% lower than the target of 90%, even from year to year it decreased. Factors that influence the coverage of postpartum maternal health services are the distance of the house to health facilities and family support. The purpose of the study was to determine the relationship between the distance of houses to health and family support facilities with contact with postpartum mothers in the working area of the Tatah Makmur Community Health Center in Banjar Regency year 2019. This research method uses an analytical survey design with a cross sectional approach. The variables in this study were childbirth mother contact, Distance of Mother Nifas's Home to Family Health and Support Facilities. The population in the study of all postpartum mothers was 226 postpartum mothers in the working area of the Tatah Makmur Health Center in 2019. The purposive sampling technique was 70 people. The instrument used was a questionnaire. Data analysis using Chi-Square statistical test with α 0.05. The results of the study showed that from 70 respondents showed Contact Nifas as many as 45 (64.3%) respondents. As many asfrom distance to the distant health facility 37 (52.9%) respondents,received family support 40 (57.1%) respondents. Thestatistical test Chi-Square shows that there is a relationship between the Distance of the House to the Health Facility (ρ 0.002) and Family Support (ρ 0.004) with the Contact of Nifas. The conclusion of the study is that there is a relationship between the distance of the house to the family health and support facilities and contact with Nifas. Keywords: Contact Ms. Nifas, Distance of Houses to Health Facilities, Family Support